Deficits of hot executive function in developmental coordination disorder: Sensitivity to positive social cues - Rahimi-Golkhandan, S.; Steenbergen, B.; Piek, Jan; Wilson, P. (Elsevier BV; North Holland, 2014)
Recent research shows that children with motor coordination problems (or developmental coordination disorder – DCD) show deficits in not only cool executive function (EF), but also hot EF. We aimed to determine whether this deficit of hot EF is due to heightened sensitivity to rewarding stimuli, specifically, or to a general deficit of cognitive control, like inhibition. Using two versions of a go/no-go task, one with neutral facial expressions and the other with happy and fearful faces, we compared 12 children with DCD with 28 typically-developing children, aged 7–12 years. Like earlier studies, children responded faster to happy faces. Both groups showed comparable accuracy in response to go targets, and also had similar commission errors, except when the no-go stimulus was a happy face. Importantly, the DCD group made significantly more commission errors to happy faces failing to suppress their response on more than half of the no-go trials. These results suggest a heightened sensitivity to emotionally significant distractors in DCD; this type of impulsivity may undermine self-regulation in DCD, with possible implications for adaptive function and emotional well-being. We argue that the interaction of cognitive control and emotion processing networks may be disrupted in DCD or delayed in development.